2022
DOI: 10.26603/001c.34417
|View full text |Cite
|
Sign up to set email alerts
|

Single Leg Bridge Test is Not a Valid Clinical Tool to Assess Maximum Hamstring Strength

Abstract: Background The single leg bridge test (SLBT) has been introduced in the sports context as a way of estimating hamstring muscle capacity for prevention and rehabilitation of hamstring strain injuries. Purpose The primary aim was to examine the association between SLBT scores with concentric and eccentric knee flexor peak torques. Secondarily, this study aimed examine the association of between-limb asymmetries provided by SLBT and isokinetic tests. Study design Cross-sectional study. Methods One hundred m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The intervention was carried out for 6 weeks, three times per week. Sit and reach test (9), Passive knee extension test (PKET) (10,11), Single leg bridge test (SLBT) (12,13), and Leg dynamometer (LD) were used to determine changes in hamstring muscle before and after the intervention series HSIC…”
Section: Methodsmentioning
confidence: 99%

Exercises for Hamstring Tightness

Sondang Irawan,
Khalifatul Husna,
Fathoni
et al. 2023
Kme
“…The intervention was carried out for 6 weeks, three times per week. Sit and reach test (9), Passive knee extension test (PKET) (10,11), Single leg bridge test (SLBT) (12,13), and Leg dynamometer (LD) were used to determine changes in hamstring muscle before and after the intervention series HSIC…”
Section: Methodsmentioning
confidence: 99%

Exercises for Hamstring Tightness

Sondang Irawan,
Khalifatul Husna,
Fathoni
et al. 2023
Kme
“…One study found that an isometric hip extension exercise leads to greater improvements in the single-leg hamstring bridge to fatigue test compared with the NHE (17). However, the single-leg hamstring bridge to fatigue test is not a valid measure of hamstring strength (18), and this study did not investigate sprinting performance or muscle architecture. In a more recent study (19), an isometric hip extension exercise was shown to improve isometric hamstring strength but failed to significantly change BFlh fascicle length.…”
mentioning
confidence: 99%